Responses of Indo-Pacific humpback dolphins (Sousa chinensis) to construction of the Hong Kong–Zhuhai–Macao Bridge - Huang, Zhixiong; Fang, Liang; Wen, Hua; Zhang, Kui; Wang, Xinxing; Chen, Tao (Frontiers in Marine Science, 2024)
The location of offshore and coastal marine engineering projects often shows considerable overlap with the foraging and breeding grounds of marine mammals. Lingding Bay, located in the Chinese Pearl River Delta, is home to the world’s largest known population of Indo-Pacific humpback dolphins (Sousa chinensis). The bay is also the site of the Hong Kong–Zhuhai–Macao Bridge mega-engineering project. This study assessed the responses of the dolphins to the bridge construction. Data were collected on dolphin sightings by survey vessels following standard line-transect tracks, with surveys conducted during the pre-construction (2005–2006), construction (2015–2016), and post-construction (2020–2021) phases. The dolphin distribution patterns, density, group sizes, and presence of calves were compared across these three periods. Additionally, the range patterns of the dolphins were analyzed following the identification of individuals during the post-construction phase. The average distance at which humpback dolphins were sighted from the bridge was significantly shorter after the completion of the bridge than during the pre-construction and construction phases. Furthermore, the density of humpback dolphins in the southern region of the bay—where the bridge is located—was significantly higher post-construction compared with that recorded during the pre-construction and construction phases. A noticeable increase in dolphin group sizes post-construction may indicate a shift in foraging strategy. The post-construction phase coincided with the COVID-19 pandemic lockdown period, and the resultant reduced human activity in Lingding Bay may have influenced the distribution of dolphins and other animals to some extent. Individual identification results demonstrated that the waters near the bridge remained an integral habitat for the dolphins post-construction, as they freely traversed underneath the bridge. The results of this study hold considerable importance within the realm of marine engineering, offering valuable guidance and references for informed decision-making and operational practices in associated domains.